Implementation of Integrated Health Services for Post-Disaster Communities in Agam Regency, West Sumatra, Indonesia - Shirly Gunawan; Noer Saelan Tadjudin; Alexander Halim Santoso; Yohanes Firmansyah; Daniel Goh; Belinda Angie; Anggita Tamaro; Irvan Baharits Al Basith; Djulia Djulia; RA Rengganis Ularan; Hetty Karunia Tanjungsari; Mei Ie; Alicia SariJuwita (CV Media Inti Teknologi, 2026)
Background of study: The natural disaster in Agam Regency, West Sumatra, have disrupted access to health services and increased the risk of acute illness, exacerbating chronic illnesses, and causing psychosocial problems. This situation demands a rapid, integrated, and adaptive health response to the limitations of post-disaster facilities. This community service activity aims to improve access and quality of health services for disaster- affected communities through an integrated approach to medical services and logistics distribution. Methods: The program was implemented over three days at several locations and health posts in Agam Regency. Activities included cross-sector coordination, implementation of health services, daily evaluation, reporting, and planning for sustainability. Interventions included basic and advanced medical services, post-operative wound care, chronic disease management, home-visits, and medical assistance. Result: Health services were provided for more than 200 patients, predominantly with cases of hypertension, upper respiratory tract infections, dermatitis, musculoskeletal disorders, and diabetes mellitus. The home visit approach successfully reached vulnerable groups with limited mobility. Conclusion: The use of simple health technology and family involvement improved continuity of care and community empowerment. This program has supported physical health recovery in post-disaster communities and has the potential to be replicated in other disaster-affected areas.